The role of personal relationships during supply chain disruptions - Cees J. Gelderman; Rens Bruggink; Janjaap Semeijn; Richard Holman (The Central European Review of Economics and Management (CEREM), 2024)
Aim: Research on supply chain disruptions is most commonly conducted on the inter-organizational level of analysis. Although personal relationships in business-to-business relationships are generally considered important, the role of personal relationships during supply chain disruptions has been neglected in extant literature. Our study aims to fill this void by focusing on the role of personal relationships from the buyer perspective. Design / Research methods: An embedded case study was conducted at manufacturer ASML on the role of personal relationships during seven supply chain disruptions. ASML is the world's leading supplier of machines for the semiconductor industry. The unit of analysis is a supply chain disruption due to a delay or interruption in supply caused by the supplier or a sub-supplier. A total of seven sub-cases were examined. Conclusions / findings: We found that personal relationships facilitate communication, the building of trust, flexibility, mutual understanding and anticipating behaviors. The results indicate that personal relationships indeed can play an important role in advancing supplier performance and addressing supply chain disruptions. Originality / value of the article: The lack of research into the role of personal relationships in handling supply chain disruptions is a notable omission and points to a gap in the current body of knowledge. This study contributes to current understandings and knowledge by being one of the first studies to specifically investigate the role of personal relationships in a context of supply chain disruptions. Implications of the research (if applicable): The results of this study have important implications for practice. The recommendation for management is to make employees aware and train them to invest in personal relationships which lays the foundation for successful collaboration also on the inter firm level. Trust and communication can be reinforced by regular face-to-face meetings, team-building activities with counterparts and communication training for better personal skills. Regular communication and maintaining relationships in stable times can help to increase supply chain resilience. Limitations of the research: A limitation of this research is its focus on describing the role of personal relationships during different supply chain disruptions within a single focus organization. Another limitation of our study is the focus on supply chain disruptions that were successfully resolved. Further research could address these issues.
Keywords: L63; M5; 330; personal relationships; supply chain disruptions; personal communication; proactive measures; reactive measures